Tempo e trabalho docente nas pesquisas acadêmicas da região centro-oeste sobre educação integral e escola de tempo integral - Dias, Jéssica França (2015)
This research aimed to study the concepts of time and teaching of academic research on integral education and full-time school produced in post graduate programs in Education of the Midwest region of Brazil. The questions that guided this research were: How the time and teaching concepts have been problematized and analyzed in academic research on comprehensive education and school full time? Relations and contradictions that exist between time and teaching in public school full-time? The research was bibliographical nature and sources were the theses and dissertations on comprehensive education and full-time school of graduate programs in Education in the Midwest Region. For the identification and analysis of theses and dissertations elected as the time frame from 2008 to 2014 productions, taking the More Education Program, implemented in 2007, as a milestone. We presented in the dissertation an analysis of the concepts of integral education, full-time school and expansion of school time related to the historical-political argument public full-time school in our country. They were identified and analyzed the concepts of time and teaching work of research, relating them to the issue of working time and school time in capitalist society. From these analyzes we present a reflection on the limits and possibilities of expanding the school day and teaching work at the full-time school from a gramscian perspective of education and school.